Preparing School Principals for a Diverse and Changing World - Gilbert Davila (Educational Considerations, 2009)
The mission of the School of Leadership Studies at Kansas State University is to develop “knowledgeable, ethical, caring, inclusive leaders for a diverse and changing world."
Keywords: Inclusive; leadership; standards; intercultural; competence; cultural; schools; principals; change; world